PENINGKATAN PENALARAN ILMIAH SISWA MELALUI PEMBELAJARAN GUIDED INQUIRY BERSTRATEGI SCAFFOLDING PADA MATERI SUHU DAN KALOR - Sundari, Putri Dwi; Rimadani, Ety (JURNAL EKSAKTA PENDIDIKAN (JEP), 2020)
The purpose of this research was to analyze the students? scientific reasoning skills in the guided inquiry learning integrated of scaffolding in heat and temperature. The research used mixed-method with embedded experimental design. The subject of this research was 29 students of class X in Sidoarjo state high school. The instrument consists of treatment and measurement instruments. The treatment instruments consist of syllabus, lesson plan, and student worksheet. The measurement instrument consists of scientific reasoning skills test. The test development based on scientific reasoning pattern proposed by Lawson with a reliability of 0.848. The quantitative data on students? scientific reasoning skills was analyzed using Wilcoxon-test, while qualitative data was analyzed by reducing data and coding using a scientific reasoning pattern rubric. The results show that students? scientific reasoning skill in heat and temperature increased after following the guided inquiry learning integrated of scaffolding. The students have been able to use information to determine whether a conclusion is likely to be true or not, but students are still unable to recognize and interpret relationships in situations described by observed or abstract variables.